THE EFFECT OF THE AMOUNT OF FEED ON THE BIOLOGICAL INDICATORS OF THE SILKWORM AND ON THE INDICATORS OF THE SILKWORM - Yakubov Gulomjon Bahadir son (International Journal on Orange Technologies, 2021)
It was found that during the worm formation period, the viability of larvae when feeding silkworm larvae with mulberry varietal leaves with 1000 kg of leaves per 1 box is 94.5-95.0%, and when stealing mulberries by feeding mulberry varietal leaves to worms-1450 mg, and the volume is 1470 cm. It follows from this that during the larval life of silkworms, it is advisable to feed as many varietal mulberry leaves as possible.